LIVING QURAN DALAM RITUAL PERTANIAN DI GAMPONG WAIDO, KABUPATEN PIDIE, ACEH - Al-Hafi, Aban; Husin Lubis, Zakaria; Nurbaiti, Nurbaiti (Institut PTIQ Jakarta, 2023)
The issue addressed in this research originates from the implementation of classical religious traditions within modern farming communities in Gampong Waido. The primary objective of this study is to comprehend the extent to which the Quran becomes an integral part of the agricultural rituals perpetuated by the community, as well as to unearth the significance of this tradition in their daily lives. This research adopts a qualitative approach with a focus on field research. The research methods employed include ethnography and the Living Quran approach. The research findings elucidate that the application of verses in the khanduri blang ritual manifests in three forms: written recitations, talismans, and is classified into exegetical reception, where the community interprets Surah al-Baqarah/2:261 as the “agricultural verse.” Additionally, there is aesthetic reception, wherein the verses materialize in tangible forms with elements of beauty. Furthermore, there is a functional reception where the verses are utilized as remedies by the farmers. Moreover, these traditions and rituals serve as symbols that imbue meaning into the community's life, interpreted as expressions of mutual support, ancestral prayers, gratitude, blessings, and protection against adversity. Based on the analysis above, it is concluded that the Quranic verses manifested in the khanduri blang ritual are a tangible reflection of the Living Quran